Prešernova ribniška travma - Zavrl, Andrej (Slavistična revija, 2020)
During his schooling in Ribnica (1800-12), France Prešeren is reported to have experienced something that caused him deep and lifelong distress. This article provides a comprehensive overview of the sources used to interpret the poet's experience in Ribnica and analyses their interpretations in scholarly and fictional biographies of Prešeren. After their examination, the author concludes by proposing his answer to the question of what trauma young Prešeren suffered.
Keywords: biografije; izobraževanje; Prešeren, France; Ribnica; slovenski pesniki; travme